Pre-menstrual Syndrome and Pre-menstrual Dysphoric Disorder in Female Medical Students of Nepal - Mahat, A; Dhungana, R; Amatya, A (Kathmandu University Medical Journal, 2023)
Background Pre-menstrual Syndrome and Pre-menstrual Dysphoric Disorder can have negative impact on medical students and remains mostly underdiagnosed. Different treatment modalities like medications (doctor-prescribed or self-medicated), and alternative therapies are used by students to cope with pre-menstrual symptoms. Objective To estimate the prevalence and severity of Premenstrual Syndrome and Premenstrual Dysphoric Disorder among medical students in Nepal along with its impact in their quality of life, their health seeking behavior and treatment modalities used to cope with these disorders. Method A cross-sectional study was conducted among female medical students studying MBBS in various medical colleges in Nepal using a self-administered questionnaire from September 2020 to March 2021. Result The prevalence of Premenstrual Syndrome and Premenstrual Dysphoric Disorder among female medical students in Nepal was 64% and 36.3% respectively as per this study. Among the areas impacted by premenstrual symptoms, concentration in class was the most affected (68.1%), followed by distress (64.6%). Only 7.3% of the responding participants sought medical consultation for their symptoms. Among those who suffered from at least one symptom for any length of time, 34.8% of participants reported of using at least one medication (either prescribed or self-medication). Similarly, alternative remedies were used by 44.4% of the participants. Conclusion Premenstrual syndrome and premenstrual dysphoric disorder were found to be common in female medical students of Nepal. However, very few students sought medical consultation despite a significant impact in their academic and other activities. Self-medication and traditional therapies were common modalities used for treatment of premenstrual symptoms.